Exploring students’ needs for vocabulary games in learning Arabic for business purposes - Ahmad, Nor Zahidah; Wan Mahmud, Wan Marfazila; Abd Wahid, Najihah; Nordin, Fitri Nurul'ain; Ahmad Safian, Nursafira (Human Resource Management Academic Research Society, 2025)
This study was conducted to examine students’ needs regarding the use and development of an Arabic vocabulary game for business purposes. The background of this research lies in the growing importance of Arabic as a global business language, especially in trade and commerce involving the Middle East and other Arabic-speaking regions. Despite this, many students still face challenges in mastering business-related vocabulary, which highlights the need for effective learning tools to enhance vocabulary acquisition. The objective of this pilot study is to investigate students’ needs for the development of the Arabic vocabulary board game prototype “I-Mufradaat,” utilizing a vocabulary-based board game as an innovative approach to learning Arabic for business purposes. The research employed a survey design, with data collected through questionnaires administered to 45 undergraduate students in the field of business at Universiti Teknologi MARA (UiTM), Shah Alam. Findings indicate that learners expressed a strong need for engaging and gamified resources to supplement traditional methods, emphasizing motivation, interactivity, and contextual application. The results provide valuable preliminary insights for refining the design and content of I-Mufradaat, supporting its potential as an effective gamification-based tool to enhance Arabic vocabulary acquisition among non-native speakers. In conclusion, this study emphasizes the potential of vocabulary games as an innovative and interactive medium for enhancing Arabic learning in business contexts. It also suggests the development of gamified products as practical teaching aids to bridge the gap between students’ needs and effective learning strategies.